Religious Beliefs And Humanitarian Law With Special Reference To Islam - Ibrahim, Ahmad (Journal of Malaysian and Comparative Law, 2019)
Asia has been the birthplace of many religions which are now being followed by millions of people all over the world. Religion, tradition and custom have many variesties in the cultures of the world. It is true that in some cases these diversities led to differences and are the cause of conflicts. However diversity in Asia can be an asset, just as the various instruments of an orchestra can produce a wonderful harmony. There is no religion which advocates hatred and killing. Religion should show the importance of love and compassion. All religions more or less speak about the same ideal, namely to lift man to such an ideal position that he can live in a state of natural peace, prosperity, justice and dignity.